Review And Assess The Optimal Arrangement Of Viscous Dampers In Order To Reduce The Seismic Response Of Tall Reinforced Concrete Structures - Vafaei, Ashkan; Lou, Ashkan Khoda Bandeh (The Turkish Online Journal of Design Art and Communication, 2016)
In recent years, the call control structures in earthquake using energy dissipating devices such as dampers have been of particular importance. Research has shown that the use of viscous dampers can play an effective role in monitoring the response of structures against the wind, explosion and earthquake. The optimal arrangement is very effective damper efficiency of their performance. In this study, design is ideal viscous damper damping operation for 100 percent and put it in different modes in structures using software ETABS2015 try to determine whether the optimal model can be offered to install dampers in plan and elevation classes, to be answered. The model used in this study is a 20-storey reinforced concrete three-dimensional structure of the records used for non-linear time history analysis of earthquake KOBE and SMART1 and are LANDERS. The results show the effect of the optimal arrangement of viscous damper in reducing the seismic response of structures. However, the optimal location for a viscous damper structure under different earthquake quake because of different characteristics vary. Therefore, it can be a hundred percent for the optimal location pattern presented viscous dampers. LANDERS structures under earthquake model in this study will have the seismic response of the maximum amount of 43.02 percent compared to non-damper. However, in most cases, the best structural response is the time when the dampers in building frames with each other in adjacent springs are installed.
Keywords: Viscous Damper; Seismic Response; ETABS; Time History Analysis; Records